2002
DOI: 10.1002/cjce.5450800213
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics of gas fluidized beds with mixture of group D and B particles

Abstract: The dynamics of a gas‐solid fluidized bed containing Geldart Group D particles mixed with a small proportion of Geldart Group B particles are investigated using pressure fluctuations data. Time series analysis, using a variety of nonlinear dynamics tools, shows that the slugging present with Group D particles can be suppressed by the addition of a small proportion of Group B particles. The power spectra and the auto‐correlation function are used for a preliminary evaluation of dominant slug frequencies. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…According to Ajbar et al [8], the mixing of particles belonging to different Geldart's classification groups could introduce some interesting behaviour that is not found for single-group fluidization. For example, by adding a small proportion of Group B-particles to a Group D-particle bed, the famous character of coarse particle fluidization (slugging) can be significantly suppressed [27].…”
Section: Introductionmentioning
confidence: 99%
“…According to Ajbar et al [8], the mixing of particles belonging to different Geldart's classification groups could introduce some interesting behaviour that is not found for single-group fluidization. For example, by adding a small proportion of Group B-particles to a Group D-particle bed, the famous character of coarse particle fluidization (slugging) can be significantly suppressed [27].…”
Section: Introductionmentioning
confidence: 99%
“…The mixing can alter in a substantial way the dynamics of the gas-solid system. For instance, in a previous study (Ajbar et al, 2002) on gas fluidization behaviour of coarse particles, it was shown that the addition of a small proportion of group B to existing group D particles can significantly reduce the slugging that is a characteristic of fluidization of coarse particles.…”
mentioning
confidence: 99%
“…Dilute-phase flow and dense-phase slugging flow regime models were verified for this system by Sivasanmugam and Lakshmi. 3 Ajbar et al 4 studied the hydrodynamic behavior of Geldart group D particles mixed with a small proportion of Geldart group B particles using pressure fluctuations data. Recent research on the hydrodynamics and mixing of biomass particles in fluidized beds has been reviewed by Cui and Grace.…”
Section: Introductionmentioning
confidence: 99%